[Letter from Samuel D. Chilcote Jr. outlining efforts by other organizations to oppose proposed excise tax increase] (Tufts Archival Research Center, 2007)
Letter from Samuel D. Chilcote Jr. to the Executive Committee of the Tobacco Institute regarding a proposed increase in excise taxes. Includes the activities of many organizations also opposed to increased excise taxes as well as activity within Congress and state Legislatures regarding this issue.